Evaluation of Acid-Suppressive Medications Prescribing and Usage in Central Hospitals in Abha Region, Saudi Arabia - Khaled M. Alakhali; Hadeel M. Bayoumi; Elham S. Abunakhaa; Manal Ahmed; Nada S. Alqahtani; Rasha A. Jaber; Sahar S. Alasmari; Subhya A. Alshahrani; Zohoor A. Alshahrani
ABSTRACT Objective: The aim of this study was to study and assess the indications of acid suppressive drugs and to find out percentage of irrational prescriptions with acid suppressive drugs. Material/Methods: It is a prospective observational study conducted in the Armed Forces Hospitals Southern Region and Abha Maternity Hospital, both in Abha in Assir region (Saudi Arabia). The sample size of study was 185 patients. The case sheets of the patients' prescription order were reviewed for acid suppressive drugs prescription and relevant data was taken. Patients' age above 18 were identified. The duration of study was 8 weeks, between May and June 2017. Results: Our results showed that the majority of the prescriptions of proton pump inhibitors (68.1%) were unjustifiable and that proton pump inhibitor was the most commonly prescribed acid suppressive drugs for the patients (97.8%). The frequency of prescribing for the autism spectrum disorders in our study was found to be higher in patients with an existing risk factor and was mostly recommended by physicians as concomitant medications (67.6%). The most common concomitant medications used with the proton pump inhibitors were non-steroidal anti-inflammatory drugs (29.2%) in which aspirin composed 13.5% of the non-steroidal anti-inflammatory drugs prescribed followed by antimicrobials (9.2%). Conclusion: Acid suppressive drugs are the most commonly prescribed drugs with no proper indications hence irrational. Based on the results of this study, creating awareness about reasonable use of acid suppressive drugs is a necessity.